Collaborative Program in Educational Administration at Kansas State University and Fort Hays State University is Established - Charles E. Litz; Gerald D. Bailey (Educational Considerations, 1987)
The faculties in the educational administration programs at Kansas State University and Fort Hays State University have entered into an agreement to facilitate the post-master's degree programs of graduate students admitted to the collaborative program.